The Motor Rangers' Cloud Cruiser - Goldfrap, John Henry, 1879-1917; Wrenn, Charles L. (Charles Lewis), 1880-1952 (Salt Lake City, UT : Project Gutenberg, 2015)
"The Motor Rangers' Cloud Cruiser" by Marvin West is a fictional adventure novel written in the early 20th century. It follows the escapades of a group of adventurous boys known as the Motor Rangers, particularly focusing on their leader, Nat Trevor, and his friends, Joe Hartley and William "Ding-Dong" Bell, as they navigate treacherous seas after departing from the Marquesas Islands. The story promises to be filled with thrilling discoveries, mechanical challenges, and unforeseen dangers in the vast Pacific Ocean. At the start of the narrative, the Motor Rangers aboard their vessel, the "Nomad", face turbulent weather conditions while approaching an intriguing island that seems to defy the navigational charts. Nat's leadership is put to the test as he and his friends grapple with powerful ocean currents drawing them toward a mysterious passage between two volcanic islands. As they brave the mounting storm, Joe is swept overboard, prompting Nat to make a daring rescue. The intensity of the unfolding situation hints at greater volcanic perils that await the trio, setting the stage for a whirlwind of encounters and future adventures. (This is an automatically generated summary.)
Release date is 2015-02-15
E-text prepared by David Edwards, Rick Morris, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Islands -- Juvenile fiction; Mystery and detective stories; Airships -- Juvenile fiction; Boats and boating -- Juvenile fiction